Predicting Surgical Outcomes in Pituitary Adenomas: The Role of Radiological Classifications - Fareeha Nisar; Mubashirah Charolia; Mehar Masroor; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2026)
Pituitary adenomas are common sellar tumours in which transsphenoidal surgery is often the main treatment. Surgical resection largely depends on extrasellar extension, especially cavernous sinus involvement, making radiological classifications important for operative planning and patient counselling. This review summarizes evidence on the Hardy-Wilson and Knosp classifications (including revised Knosp) for predicting extent of resection. Hardy-Wilson grading describes sellar changes and suprasellar extension but has limited value for assessing parasellar invasion on modern MRI. The Knosp classification, based on the tumour’s relationship to the internal carotid artery, more directly estimates cavernous sinus invasion and correlates with gross total resection rates. Studies consistently show reduced resection and remission with higher Knosp grades, while the revised Knosp subdivision (3A/3B) improves its predictive value. Overall, revised Knosp is more reliable for outcome prediction in contemporary endoscopic practice.